In situ demonstration of tissue proliferative activity using anti-bromo-deoxyuridine monoclonal antibody. Issue 8 (August 1989) - Veronese, S; Gambacorta, M; Falini, B
Abstract : Immunohistochemical staining with anti-bromo-deoxyuridine (BrdU) monoclonal antibody was performed on a variety of human tissues following in vitro incubation with BrdU. The effect of different fixatives and DNA denaturation techniques on the reactivity with anti-BrdU was investigated. Optimal preservation of the antigenicity of BrdU incorporated into the DNA of proliferating cells was seen in tissues fixed in Bouin's fluid, while samples which had been fixed with cross-linking reagents, such as formalin, were usually unreactive. Positivity for BrdU was restored in formalin fixed tissues after digestion with pepsin, but this was usually associated with loss of morphological details. Acid and thermal DNA denaturation techniques gave similar results. It is concluded that Bouin fixation followed by acid or thermal denaturation of DNA is the method of choice for the in situ detection of cells in S-phase using anti-BrdU monoclonal antibody.